Episodic envy and counterproductive work behaviors: Is more justice always good?. (29th April 2013) - Khan, Abdul Karim; Quratulain, Samina; M. Bell, Chris
Summary The authors examined how perceived event‐specific procedural and distributive justice about own and envied others' outcomes interacts with episodic envy to predict counterproductive work behaviors. Our results were consistent with the attribution model of justice, finding that episodic envy significantly predicted counterproductive work behaviors aimed at envied others in the workplace and that this relationship was more pronounced when perceptions of procedural, but not distributive, justice about own or envied others' outcomes were high rather than low. We tested a moderated‐mediation model in which self‐attributions for the outcome mediated the effect of episodic envy on counterproductive work behaviors and that the effect of envy was stronger when perceptions of own or others' procedural justice were high rather than low. This research contributes to the literature on envy processes in the workplace and is the first to use a specific emotion, envy, as a proxy for a negative outcome in a demonstration of the attribution model of justice. Copyright © 2013 John Wiley & Sons, Ltd.